Laparoscopic Sacrocolpopexy or Sacrohysteropexy with or Without Burch Colposuspension: The Results of 36 Patients in Our Clinic - İlknur İnegöl Gümüş; Önder Sürgit; Nilüfer Akgün; İkbal Kaygusuz; Deniz Hızlı (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Our aim was to investigate the results and the effectivity of laparoscopic sacrocolpopexy or sacrohisteropexy with or without Burch colposuspension in pelvic organ prolapse with or wihout urinary incontinence patients in our clinic.